Change In Demographic Profile of Carcinoma Endometrium – An Analysis from A Tertiary Care Centre - Rutwika, Chandu; Kandasamy, Vijayalakshmi; Ajmal, Imran Thariq; Raj, Felix Anand (Journal of Neonatal Surgery, 2025)
Background: The incidence of carcinoma endometrium is rising worldwide, with marked demographic shifts driven by urbanisation, longevity and metabolic disease. Indian data remain sparse, particularly on the interplay between sociodemographic factors and aggressive histotypes. Methods: We performed a retrospective cross‑sectional review of 25 consecutive women managed for carcinoma endometrium between August 2022 and August 2024 in a tertiary referral hospital in southern India. Demographic variables, reproductive history, socioeconomic status, imaging, histopathology (WHO 2014) and Fédération Internationale de Gynécologie et d’Obstétrique (FIGO 2018) stage were abstracted. Descriptive statistics, χ² tests and Pearson correlations explored associations; significance was set at p < 0.05. Results: Median age was 58 years (IQR 52–65); 72 % were post‑menopausal and 84 % multiparous. A lower‑socioeconomic background characterised 72 % of patients. Endometrioid carcinoma predominated (64 %), but high‑risk subtypes—serous and clear‑cell—collectively accounted for 28 %. One‑fifth of tumours were poorly differentiated (Grade III). Advanced (Stage III–IV) disease presented in 32 % of women. Tumour grade correlated significantly with lymphovascular invasion (r = 0.62, p < 0.001), and serous histology correlated with advanced stage (r = 0.68, p < 0.01). Conclusion: Even in a small cohort, a clear shift towards aggressive histology and late‑stage presentation is evident, disproportionately affecting socio‑economically disadvantaged women. Early detection strategies, equitable access to care and integration of molecular testing are imperative to curb morbidity